Complement C5a receptor gene 450 C/T polymorphism in renal transplant recipients: association of the CT genotype with graft outcome - Günesacar, Ramazan; Opelz, Gerhard; Erken, E.; Döhler, Bernd; Ruhenstroth, Andrea; Süsal, Caner (Tissue antigens, 2015)
Complement-mediated humoral rejection has become the main focus of research in organ transplantation. The aim of this study was to investigate the possible association of the complement C5aR gene 450 C/T polymorphism in antibody-mediated renal allograft rejection. This polymorphism was investigated in 290 first deceased donor kidney graft recipients with well functioning grafts and no rejection treatment during the first transplant year (WFG), 265 recipients with graft failure within the first transplant year (F), and 187 healthy controls. Frequency of the 450 CT genotype was lower in the total population of 555 kidney recipients (4.7%) than in 187 healthy controls (8.6%), but the difference was not statistically significant (P = 0.065). A significantly higher frequency of CT genotype was found in F patients (CT: 6.8%) when compared to WFG patients (CT: 2.8%, P = 0.027). The CT genotype was also significantly lower in WFG patients than in healthy controls (P = 0.009). Low frequency of the C5aR 450 CT genotype, which apparently is a feature of certain kidney diseases, appears to be associated with good graft outcome in kidney transplantation and might be helpful for identifying recipients who are at low risk for graft rejection.
Gesehen am 27.01.2021